Digestibility of Heat Treated Barley in Blue Fox and Mink - Korhonen, Hannu T; NiemelÃƒÂ¤, Paavo (EDUCARE, 2014)
ABSTRACT: Carbohydrates are easy accessible raw material for fresh feed in domestic animal production. Barley, which mainly contains carbohydrates, has become more popular as an ingredient in feed for fur bearing animals in particular. The aim of the present study was to clarify the effects of heat treatment on digestibility of barley in farm-raised juvenile blue fox and mink. Two different heat treatments were compared here: (1) traditional heat treatment; and (2) specific treatment, including exposure to pressure and heat, and by gelatinization. Experimental animals were six adult males of dark standard-type mink or âneovison visonâ and blue fox or âvulpes lagopusâ. The digestibility was evaluated by the AIA indicator method with 0.5 silicate (celite 545) serving as an inert indicator. Main components in the study feed were slaughter-house offal, Baltic herring, barley, and water. Ash content was higher in specific than in traditional diet (p < 0.001). Crude protein content tended to be slightly higher in specific diet. In blue fox and mink, digestibility of crude protein and fat were similar in traditional and specific diet (p > 0.005). Digestibility of carbohydrates and organic matter was significantly (p < 0.01) better for specific than traditional diets. Heat treatment including gelatinization can be recommended to use for better utilization of carbohydrate stuff in the diet.KEY WORDS: Farmed furbearers, mink and blue fox, heat treatment, feed ingredients, fur farming, carbohydrate, and digestive value.Â Â About the Authors: Prof. Hannu T. Korhonen, Ph.D. and Paavo NiemelÃ¤, Ph.D. are Principal Research Scientist and Docent in Applied Zoology at the MTT Agrifood Research Finland, Animal Production Research, SilmÃ¤jÃ¤rventie 2, Â FIN-69100 Kannus, Finland. For academic purposes, corresponding author is: hannut.korhonen@mtt.fiHow to cite this article? Korhonen, Hannu T. & Paavo NiemelÃ¤. (2014). âDigestibility of Heat Treated Barley in Blue Fox and Minkâ in EDUCARE: International Journal for Educational Studies, Vol.7(1) August, pp.43-48. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (March 20, 2014); Revised (May 30, 2014); and Published (August 17, 2014).